Revisiting the Co-Occurrence of Intimate Partner Violence and Child Maltreatment - Tullberg, Erika (Journal of interpersonal violence, 2023)
Child welfare (CW) agencies are charged with ensuring children’s safety; when children live with families impacted by intimate partner violence (IPV), this task can be complex. To better understand how U.S. CW agencies identify and make decisions about child maltreatment (CM) in the presence of IPV, this mixed-methods study used national data (N = 248,654) to investigate whether IPV was more likely to be documented as co-occurring with certain types of CM. This study also explored the intersection of IPV and CM using 19 semi-structured interviews with child welfare stakeholders to gain insight into the mechanisms underpinning reporting processes. Multinomial logistical regression showed that after controlling for other risk factors, children living in a household with IPV were more likely to be determined to be physically abused and emotionally maltreated than neglected, and less likely to be determined to be sexually abused than neglected, compared with children who did not live in a household with IPV. Those children were also more likely to be determined to be emotionally maltreated than physically abused, and less likely to be determined to be sexually abused than physically abused, compared with children who did not live in a household with IPV (all results, p < .0001). Qualitative results revealed IPV and children’s exposure to IPV may be categorized as different types of CM by CW agencies and staff, and that this categorization can vary by agency and staff level. Participants also described challenges to addressing IPV within CW systems. Findings suggest national CW data may obscure when IPV and CM co-occur versus when a given type of CM is serving as a proxy for the presence of or children’s exposure to IPV, presenting challenges to interpreting child welfare data. Recommendations are presented to improve CW data accuracy and ensure the safety of children and families impacted by IPV.